Transition-Metal-Free Aerobic Oxidative Cross-Coupling of Indoles with Arylidenemalononitriles - Yang, Aizhen; Li, Zheng (Synlett, 2020)
An efficient method for the direct construction of C(sp2)–C(sp2) bonds by aerobic oxidative cross-coupling of indoles with arylidenemalononitriles is described. Various [aryl(1H-indol-3-yl)methylene]malononitriles were efficiently synthesized by using air as an oxidant under mild conditions. The salient features for this protocol are no transition-metal catalysts, no organometallic reagents, high atom economy, high yield, mild conditions, and simple workup procedures.
Keywords: cross-coupling; indoles; arylidenemalononitriles; metal-free synthesis